Health communication by an ascribed population of a family clinic in the city of Rio de Janeiro (Research, Society and Development, 2021)
The study aims to present subsidies for the development of effective health communication strategies for an enrolled population of a basic health unit in the city of Rio de Janeiro through the realization of a situational diagnosis. This is a cross-sectional, descriptive study with a quantitative approach, using secondary data from 200 reports produced at the health unit. Information was acquired on the sociodemographic profile and health communication process of the population enrolled. The median age of the participants was 35 years old, the majority being female. The predominant level of education was incomplete primary education and income of a minimum wage. Most of the population had smartphones, television and internet access. It was found that users have Google® and Health Professionals as sources of health information used, with Google® being more expressive among men over women, who use Instagram® more. With regard to health communication strategies, age was shown to be a statistically relevant factor regarding the acceptance of health information pamphlets (p=0,005). As for fake health news, it was found that participants aged 18 to 25 years old value information checking more, however 85% of users affirmed the importance of such a procedure. Therefore, the findings contribute to the understanding of the health communication process and the planning of educational actions by primary health care professionals, highlighting its important role in this context.